A study on predictors of complete immunization in children aged 12-23 months in slums of Kanpur Nagar, India - Chaturvedi, Ruchi; Sharma, R. P.; Martolia, D. S.; Midha, Tanu (International Journal Of Community Medicine And Public Health, 2021)
Background: Kanpur is one of the major industrial hub of Uttar Pradesh. Migration of people in the search of jobs led to formation of slums in many part of city which is 20% of total population of the city. A large number of below poverty line (BPL) population (about 60%) also live-in slums. Little data is known about immunization status of children residing in these slums. With this background this study is planned to predict various demographic factors affecting immunization status and to study various factors responsible for partial/non immunization of children. Methods: Cross sectional observational study. 30 cluster sampling technique was used to select 30 clusters from 380 identified slums of Kanpur Nagar. Results: More children were completely immunized with increase in educational level of mothers. (χ2= 16.62, df=2, p=0.000) ; mothers having institutional delivery (χ2 =31.8, df=1, ,p=0.000; belonged to general category (χ2=25.3, df=2, p=0.000) and Hindu by religion. (χ2=7.34, df=1, p=.006). No significant difference was seen in immunization coverage with respect to gender (χ2 =2.7, df=1, p=.09). Obstacles (45.2%) were the most common reason for partial immunization whereas lack of information (52.63 %) was most common reason cited in case of non-immunized children. Conclusions: Educational status of the parents particularly mothers and the economic status of the family have great bearing on the immunization coverage of under 5 children. So female empowerment measures may prove helpful in improvement of the immunization status.